DESIGNING AN EFFECTIVE METHOD TO RECRUIT SALES TEAM TO INCREASE COMPANY REVENUE IN A START UP INDUSTRY - Raymond; Ginting, Henndy; Bekti , Rudy (Universitas Ibn Khaldun Bogor, 2023)
Recruiting can have the biggest impact on revenue in expanding organizations. Optimus Consulting is a local based start-up company in human resource offers executive search, recruitment process outsourcing, end-to-end mass hiring such as Management Trainee hiring program, and digital recruitment platform that helps recruiter to manage and monitor hiring process. The goal of the research is to develop a successful approach for recruiting and selecting the sales team in order to boost sales revenue. Throught a qualitative data analysis, the study found that sales team recruitment process are essential and will impact directly to the performance and the achievement of the particular sales. To address with the opportunities, Optimus should focus on improving the current recruitment process into new recruitment process with some new steps are adding into it. Some of the steps are technical assessment, simulation (case study and role play), background checking and medical check up. By addressing these opportunities, Optimus can effectively find the right sales talent to strengthen the sales team in order to increase the sales revenue and achieve its yearly target.